Factors That Influence Endometriosis to Become a Malignancy: A Narrative Review - Kusuma, Fitriyadi; Masrie, Marshaly Safira; Suryoadji, Kemal Akbar (http://dharmais.co.id/, 2026)
Endometriosis frequently affects women of reproductive age, and epidemiologic studies suggest it may be linked to an elevated risk of malignancy. Specific histopathological criteria characterise endometriosis-associated malignancy (EAM). Endometriosis-associated ovarian cancer (EAOC) accounts for about 80% of EAM occurrences, with the remaining 20% occurring outside the ovaries. Genetic mutations, including PTEN, ARID1A, and p53 alterations, are identified in endometriosis and EAM. Factors such as postmenopausal status, older age, and hypoestrogenic conditions have also been linked to higher risks of EAM and EAOC. Due to EAM's rarity, comprehensive data remains limited. This review examines current EAM research, focusing on EAOC and its clinical relevance.